Functional Outcomes After Nonoperative Management in Older Adult Low-Energy Stable and Unstable Ankle Fractures: A Retrospective Review of 158 Patients - Rebekah M. Kleinsmith MD; Fernando A. Huyke-Hernandez MD; Bailey R. Abernathy MD; Andrew Sibley BA, BS; Jordan Ammons MBA, BS; Lily Qian BA; Julie A. Switzer MD; Naoko Onizuka MD, PhD, MPH (Geriatric Orthopaedic Surgery & Rehabilitation)
Background There is ongoing debate regarding the optimal management of older adult ankle fractures. The purpose of this study was to describe baseline characteristics and functional outcomes including complications in older adult patients receiving nonoperative treatment for low-energy ankle fracture and compare the outcomes of those with unstable vs stable fracture patterns. Methods Patients aged ≥65 from January 2012 to March 2019 that sustained an ankle fracture were identified. Those who had surgical treatment, age <65, high-energy trauma, bilateral ankle fractures, and patients without adequate follow-up (minimum 12 weeks) were excluded. Baseline demographics, injury characteristics, Charlson Comorbidity Index (CCI) score, and functioning regarding ambulatory status, living environment, and assistance personnel in the household were collected for all patients. The primary outcome of interest was retention of baseline ambulation, living environment, and assistance requirements at follow-up (>12 weeks). Pain improvement, radiographic changes, and adverse clinical events were also assessed. Results A total of 158 patients were included with an average follow-up timeframe of 41.6 weeks. Eighty-six percent of patients (n = 136) retained their ambulatory status at long-term follow up. Most patients retained the same living environment (n = 145, 91.8%). Thirty-five patients (22.2%) required additional assistance long-term. Approximately 67.1% of the entire cohort retained all three functional metrics. Patients who experienced functional decline were older (77.8 vs 71.6, P < 0.001), had higher CCI (3.2 vs 1.6, P < 0.001), had a diagnosis of dementia or cognitive impairment (36.5% vs 3.8%, P < 0.001), had lower baseline functional status (ambulation, living environment, and assistance required; all P < 0.001), and had an unstable fracture pattern ( P = 0.003). Conclusions Understanding the functional outcomes of non-operative treatment in geriatric ankle fracture cases can contribute to a shared decision-making among healthcare providers, patients, and families.